Analisis Kinerja Keuangan Metode EVA, REVA dan CVA: Studi Pada Perusahaan Kosmetik di Indonesia - Resti Fauziah; Carmidah Carmidah; Thoyibatun Nisa (ARBITRASE: Journal of Economics and Accounting, 2026)
This study aims to analyze the financial performance of cosmetic companies listed on the Indonesia Stock Exchange (IDX) using the Economic Value Added (EVA), Refined Economic Value Added (REVA), and Cash Value Added (CVA) methods during the 2020-2024 period. The research objects consist of six companies, namely PT Unilever Tbk, PT Mustika Ratu Tbk, PT Martina Berto Tbk, PT Kino Indonesia Tbk, PT Akasha Wira International Tbk, and PT Mandom Indonesia Tbk. This study uses a quantitative approach with secondary data in the form of annual financial reports obtained from the official website of the Indonesia Stock Exchange and the publication of each company's financial reports. The results of the study show that based on the EVA method, PT Unilever Tbk and PT Akasha Wira International Tbk consistently generated positive EVA values ????during the study period. PT Unilever Tbk recorded the highest EVA value of 4,429,180 million rupiah in 2020, while PT Akasha Wira International Tbk showed a relatively stable positive EVA value by reaching the highest EVA value in 2024 of 242,974 million rupiah. Meanwhile, other companies tended to show fluctuating negative EVA values. Based on the REVA method, the majority of companies showed negative values. PT Unilever Tbk recorded the lowest REVA value of -108.133.559 million rupiah in 2021, while PT Kino Indonesia Tbk recorded a positive value of 289.377 million rupiah in 2023. This indicates that most companies have not been able to cover their cost of capital based on market value. Meanwhile, based on the CVA method, PT Unilever Tbk was relatively consistent in generating cash-based value added, with the highest of 2.103.693 million, althought it recorded a negative value at the end period. Other companies tended to show negative CVA values during most of the study period. This study offers novelty by integrating three value-based financial performance measurement methods, namely EVA, REVA and CVA, within a single analytical framework, thereby providing a more comprehensive assessment compared to previous studies that generally employed only one measurement method. In addition, this study addresses the limitations of prior research, as no previous studies have examined these three methods simultaneously within one analytical framework.